Fractalkine/CX3CR1 Contributes to Endometriosis-Induced Neuropathic Pain and Mechanical Hypersensitivity in Rats - Liu, Zhiming; Chen, Sisi; Qiu, Chunping; Sun, Yaqiong; Li, Wenzhi; Jiang, Jie; Zhang, Jun-Ming (Frontiers in Cellular Neuroscience, 2018)
Pain is the most severe and common symptom of endometriosis, whose underlying mechanism is poorly understood. Especially nerve sensitization, due to the limitations of general endometriosis models and sampling nerve system from patients, has become a research challenge. The chemokine-fractalkine (FKN) has been demonstrated to play a key role in various forms of neuropathic pain, while its role in endometriosis pain is unknown. Our study is to explore the function of FKN in the development and maintenance of peripheral hyperalgesia and central sensitization in endometriosis using a novel endometriosis animal model developed in our lab. After modelling, behavior tests were carried out and the optimal time of molecular changes were speculated through behavior results. Ectopic tissues and L4-6 spinal cords were extracted to detect peripheral and central roles of FKN respectively. To assess morphologic characteristics of endometriosis-like lesions as well as expression and location of FKN/CX3CR1/pp38-MAPK, H&E staining, immunostaining and western blot was performed. Moreover, inhibiting FKN expression of spinal cord was achieved by intrathecal administration of FKN neutralizing antibody to further demonstrate its function. Implanting autologous uterine around sciatic nerve caused endometriosis-like lesions and produced mechanical hyperalgesia and allodynia. FKN is highly expressed on macrophages whereas its simple receptor CX3CR1 is overexpressed on the myelin sheath of the sciatic nerve fibers. Overexpressed FKN was also observed in neurons and CX3CR1/pp38-MAPK was upregulated in activated microglia in spinal dorsal horn. Intrathecal administration of FKN neutralizing antibody not only reversed established mechanical hyperalgesia and allodynia but also inhibited the expression of CX3CR1/pp38-MAPK in activated microglia, which is essential for the persistence of central sensitization. We conclude that FKN/CX3CR1 signal pattern may become one of the mechanisms of peripheral hyperalgesia in endometriosis, to be further studied. Spinal FKN is important for the development and maintenance of central sensitization in endometriosis, and further may serve as a novel therapeutic target to solve persistent pain associated with endometriosis.